Sleep quality impacts training responses and performance in elite swimmers - Lundstrom, E. A.; De Souza, M. J.; Conklin, M. E.; Williams, N. I. (European Journal of Sport Science, 2025)
High-quality sleep is necessary for optimal health and promoting recovery from training, contributing to sport performance. Research suggests a high prevalence of poor sleep duration and quality in athletes. Reduced sleep duration has been shown to be deleterious to performance, but less is known about sleep quality and its relationship to training responses and performance. In 26 elite male (n = 10) and female (n = 16) collegiate swimmers, we assessed sleep quality (sleep duration (hrs), sleep debt (hrs), slow-wave sleep (SWShrs and SWS%), rapid-eye movement (REMhrs and REM%)), training measures (strain (AU), average heart rate (HR) (ExHRavg) and maximum exercising HR (ExHRmax)), and swimming performance (200yd time trial swim) during heavy training, preceding championship competition. Collection of sleep data was matched to days of training data collection, and also to the day preceding the performance swim. Pearson correlations were utilized to determine relationships between variables unless sex effects existed in which case linear regression analyses were utilized to control for sex differences in variables. In all swimmers, sleep duration is related to strain (R = -0.78; p = 0.01), and sleep debt is related to ExHRavg (R = 0.53; p = 0.005). SWShrs negatively is related to ExHRavg (R = -0.42; p = 0.032). Controlling for sex, sleep duration predicted swimming performance (R2 = 0.881; p < 0.001), swimmers with greater sleep durations exhibited faster swim race times. Similarly, when controlling for sex, SWS% predicted swimming performance (R2 = 0.883; p < 0.001), swimmers with greater SWS% exhibited faster times. Sleep quality measures were related to training adaptations and swimming performance was predicted by sleep quantity and quality. Athletes should obtain adequate sleep to support recovery and optimize training and performance.